2020
DOI: 10.3390/su12083198
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration Effect of Skill-Based Local Labor Pooling: Evidence of South Korea

Abstract: Since workplace skills present diverse dimensions of a worker's ability, it has recently received renewed interest by researchers examining the growth of cities. The purpose of the paper explores the advantage of regional concentrations of workers specialized in different types of skills. Specifically, the analysis estimates the agglomeration effects of skill-based labor pooling on wage levels and wage growth in South Korea. To this end, it constructs skill-based labor pool indices for cognitive, social, techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Previous studies showed that the scale eff ect, competition, and technology spillover are positive externalities of industrial agglomeration (Andersson et al, 2019;Choi, 2020), which explain the promotion effect of pharmaceutical industrial agglomeration on innovation. The results of columns ( 2), ( 4), and (6) revealed that the agglomeration of pharmaceutical development zones, represented by the medicine valley index, exerted no signifi cant infl uence on R&D investment and new product sales, and the coeffi cient of its infl uence on the number of patent applications was 0.250, which was only signifi cant at the 10 percent p-value level.…”
Section: Test Based On Traditional Innovation Indicatorsmentioning
confidence: 99%
“…Previous studies showed that the scale eff ect, competition, and technology spillover are positive externalities of industrial agglomeration (Andersson et al, 2019;Choi, 2020), which explain the promotion effect of pharmaceutical industrial agglomeration on innovation. The results of columns ( 2), ( 4), and (6) revealed that the agglomeration of pharmaceutical development zones, represented by the medicine valley index, exerted no signifi cant infl uence on R&D investment and new product sales, and the coeffi cient of its infl uence on the number of patent applications was 0.250, which was only signifi cant at the 10 percent p-value level.…”
Section: Test Based On Traditional Innovation Indicatorsmentioning
confidence: 99%
“…Shouth Koea develop agglomeration skill-based indices for cognitive, social, technical, and physical skills [13] Where these skills are also needed for teachers and students, during this pandemic, the skills to care for personal health are also skills that all parties need to have. By itself the concept of teaching and learning is directed at the concept of independence so that students can improve their cognitive, social, technical, and problemsolving skills.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Technological progress [33], skills agglomeration [34], trade [35] and other factors may cause skill polarization. Some studies revealed the phenomenon of skill polarization in the labor market while focusing on job polarization [2,27,30].…”
Section: Introductionmentioning
confidence: 99%